(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Tree wounds are the starting points that may lead to heartwood discoloration and decay caused by invading micro-organisms such as heartrot caused Phellinus pini. Phellinus pini most frequently occurs on douglas–fir (Pseudotsuga menziesii), pine (Pinus sylvestris) and spruce trees (Picea abies). According to investigations made in this area, infection by Phellinus pini entries through felling scars or broken tops when Phellinus pini fruiting bodies (conks) on other trees are realising airbone spores. When spores land on a freshly wounded stem, the infection process starts. Internal decay is often difficult to detect because only Phellinus pini conks indicate its presence. In most cases the number of conks doesn’t exceed one-two pieces on the surface of inficied Pinus sylvestris stems. When wood poles for power lines are harvested in length from 10 to 16m in wood felling areas where the average height of Pinus sylvestris trees is more than 27m, the local distribution of heartrot doesn’t exceed for more than 1.5m above and below each conk, the conk is located in the middle part of the pole length, the speeed of pruning exceeds 4m/sek, the hight level of risk exists that the damaged with heart rot wood pole will be accepted as appropriate to quality requirements toward heartrot because after pruning the presence of conk would be vanished but the top and butt surfaces of pole’s won’t indicate heartrot. The evidence of heartrot will be checked only in the technological process of debarking before impregnation when Phellinus pini conk place indicates. The purpose of this study is to predict the influence of Phellinus pini on Pinus sylvestris stems and to provide operational and safety recommendations concerning the risky assessment and management of infected felling areas in harvest planning processes.